2021
DOI: 10.1149/1945-7111/abe1db
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Silicon Content within Silicon-Graphite Anodes on Performance and Li Concentration Profiles of Li-Ion Cells using Neutron Depth Profiling

Abstract: Due to its high specific capacity, silicon is a promising candidate to substitute conventional graphite as anode material in lithium-ion batteries. However, pure silicon-based anodes suffer from poor capacity retention, mainly due to a large volume change during cycling, which results in material pulverization and other side reactions. Therefore, alternative compositions with lowered silicon content and a similar working voltage as graphite are favored, e.g. silicon-graphite (SiG), as they can reduce these vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 30 publications
3
27
0
Order By: Relevance
“… 12 , 13 Therefore, the use of silicon/graphite composite anodes with 0–20 wt % of Si nanoparticles has been favored, although it tends to increase both manufacturing complexity and cost. 14 16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 , 13 Therefore, the use of silicon/graphite composite anodes with 0–20 wt % of Si nanoparticles has been favored, although it tends to increase both manufacturing complexity and cost. 14 16 …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, pure silicon and Si oxides (SiO x ) have been investigated extensively as the theoretical specific capacity of Si-based anodes is 1 order of magnitude higher than that of graphite. However, the practical implementation of Si-based anodes for commercial applications is limited by the dramatic volume expansion of 100–300% experienced by these materials upon cycling, which results in extensive particle cracking, low initial Coulombic efficiency, and poor cycle life. , Therefore, the use of silicon/graphite composite anodes with 0–20 wt % of Si nanoparticles has been favored, although it tends to increase both manufacturing complexity and cost. …”
Section: Introductionmentioning
confidence: 99%
“…Herein, we report the preparation and characterization of a Si/hard carbon composite anode from waste biomass (corn cobs) via a simple route and without the use of activating agents, combined with the use of a sustainable cross-linked chitosan-based binder. The composite electrode is prepared by employing a relatively high Si content, with a Si:HC ratio of 3:5 (i.e., 37.5% Si in the active material) in order to provide a good balancing between structural stability and electrochemical performance, especially when considering that commercial Si/graphite anodes still cannot go beyond a Si mass content of 10–15% to maintain electrode integrity. , The cross-linked chitosan-based binder is prepared according to a method reported in the literature and employed as a greener alternative to commercial polyvinylidene fluoride (PVdF). Thanks to the synergistic effect of the hard carbon containment matrix and the cross-linked chitosan-based binder, the electrode shows a high and stable specific capacity at a rate of 1 A g –1 , together with a very good rate capability and capacity retention.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon (Si) and silicon/graphite (Si/C) composite active materials are considered the most promising candidates for next-generation negative electrodes (anodes) for lithium-ion battery (LIB) cells with high energy density and specific energy. The development of Si-based composite electrodes is driven especially by the nearly 10 times higher theoretical specific capacity of 3572 mAh g –1 compared to graphite (372 mAh g –1 ) as well as the abundance and potential low cost of the Si material . However, due to its large volume expansion/contraction upon (de)­lithiation of ∼280% and thereby pulverization of particles and extensive and continuous growth of the solid electrolyte interphase (SEI), Si-based composite electrodes are suffering from fast capacity fading and limited cycle life. , Several approaches were reported to counteract these degradation effects including the use of electrolyte additives, binder modification, protective surface coatings, prelithiation, and nano- or submicrometer-structured active materials. Liu et al reported a critical particle diameter of ∼150 nm below which cracking does not occur upon first lithiation. In addition, different studies showed that commercially available silicon nanoparticles (SiNP) can mitigate the pulverization effect. …”
Section: Introductionmentioning
confidence: 99%